Jazz in the Time of the Novel: The Temporal Politics of American Race and Culture - Barnhart, Bruce (Tuscaloosa, AL University of Alabama Press, 2013)
"Jazz in the Time of the Novel" argues that a culture's understanding of the concept of time plays a central role in its economic, social, and aesthetic affairs and that a culture arrives at its conception of time through its artistic practices. Bruce Barnhart, in "Jazz in the Time of the Novel, " shows that American culture of the first three decades of the twentieth century was shaped by the kindred rhythms and movements of two particular art forms: jazz and fiction. At the beginning of the twentieth century, widespread changes in America's social, demographic, and economic norms threatened longstanding faith in a unified and inevitable movement towards a better future. As Barnhart shows both jazz and novels of the period address these temporal uncertainties, inserting themselves into arguments about the proper unfolding of an affirmative American future. Barnhart proposes that these two aesthetic forms can be viewed as co-participants in an ongoing discussion about the way in which the future should be imagined and experienced--a discussion symptomatic of the broader exchanges taking place within the many trajectories comprising early twentieth-century American culture. This book includes in-depth approaches to numerous examples of jazz and the novel, including performances by James P. Johnson, Louis Armstrong, Bessie Smith, Duke Ellington, and Ethel Waters, and novels by James Weldon Johnson, F. Scott Fitzgerald, Ernest Hemingway, Gertrude Stein, and Nella Larsen, among others. In addition to the details of specific musical and literary works, "Jazz in the Time of the Novel" offers careful consideration as to how these works impact their social context.
Keywords: 20th Century (1901-2000); Cuckoo; Literature; Jazz; USA